Transcriptional Activation of the Factor VIII Gene in Liver Cell Lines by Interleukin-6 - Stirling, David; Hannant, Wendy A.; Ludlam, Christopher A. (Thrombosis and Haemostasis, 1998)
Circulating factor VIII (fVIII) levels increase during inflammation suggesting that fVIII synthesis or secretion is stimulated during acute inflammation. To examine the mechanisms underlying this increase in circulating factor VIII, we have developed a sensitive and reliable semi-quantitative assay for fVIII mRNA utilising competitive reverse transcriptase-polymerase chain reaction (RT-PCR, and used this to study two human liver cell lines, Hep-G2 and Chang Liver cells. These cells were cultured under basal conditions or following treatment with interleukin-1, -2 and 6 (IL-1, -2, and -6). Following 18h culture with IL-6 (maximum concentration 40U/ml), these levels had risen 6 and 9 fold respectively, with no concomitant rise in control RNA levels. The dose responses for both cell types were similar, with an ED50 of 11 U/ml. The time course of this response was also similar in both cell lines with the increase in fVIII mRNA first reaching significance by 3 h, and reaching maximum levels by 12 h. IL-1 and IL-2 had no effect at any of the doses studied. This study provides the first evidence for regulated expression of fVIII in human cell lines, and suggests that increased plasma fVIII levels during the acute phase response may be due to increased expression of fVIII mRNA.